Distribution of organic contamination of sediments from Ichkeul Lake and Bizerte Lagoon, Tunisia. Issue 1 (15th October 2017) - Ben Salem, Fida; Ben Said, Olfa; Mahmoudi, Ezzeddine; Duran, Robert; Monperrus, Mathilde
Abstract: Analyses of organochlorine pesticides (OCPs), polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and butyl tins (BuSn) were conducted on sediments from Ichkeul Lake-Bizerte Lagoon watershed (Tunisia). A total of 59 compounds (16 PAHs, 12 PCBs, 22 OCPs and 9 BuSn) were measured in 40 surface sediment samples collected during two campaigns. High concentrations of total PAHs were identified in the lagoon ranging from 122 to 19600 ng·g − 1 . Several OCPs, including endrin, dieldrin, and lindane (Hexachlorocyclohexane or HCH or BHC) were found in high concentrations in Ichkeul Lake, ranging from 28 to 2012 ng g − 1 . PAHs and OCPs varied seasonally, in response to the complex hydrology of the watershed. The concentrations of total PCBs ranged between 0.04 and 10.653 ng g − 1 and suggests low total PCBs sediment contamination, when compared to most international criteria. Total BuSn concentrations range between 67 and 526 ng·g − 1, which are relatively low when compared to most international criteria and ecological risk assessments. This is the first study of organic contamination in Ichkeul Lake (RAMSAR and UNESCO World Heritage site). Highlights: Bizerte Lagoon has stations with high concentrations of PAHs in sediments adjacent to maritime traffic. Ichkeul Lake has stations with high concentrations of four organochlorine pesticides, suspected of originating from adjacent agricultural areas. Contamination by PAHs and OCPs varies seasonally in response to the wet/dry seasonal influence of the watershed. PCBs and BuSn concentrations in sediments of the Ichkeul Lake-Bizerte Lagoon watershed are generally low to non-detected.